Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1097/scs.0b013e31815c8a68
|View full text |Cite
|
Sign up to set email alerts
|

Bitemporal Depressions After Cranioplasty for Trigonocephaly

Abstract: Long-term results after cranioplasty for trigonocephaly often show bitemporal depressions and a residual hypotelorism. Both findings fuel the perception that the growth of the periorbital region and the forehead as a whole continues to be restricted, even after correction. The aim of this study is to evaluate the growth process of the periorbital region after correction for trigonocephaly in the long term. From 1986 to 2004, 123 patients underwent a cranioplasty for the correction of trigonocephaly. Cephalomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Selber 120 found that the use of interpositional bone grafts in a series of 68 metopic children led to a decrease in the development of temporal dents. In a population of 92 trigonocephaly children in which no bone graft was used, Van der Meulen, 101 however, observed an automatic growth correction of the hypotelorism on x-ray, on account of which the use of an interpositional bone graft was judged to be unnecessary. From a photographic evaluation of 45 patients, Hilling 123 concluded that a satisfactory esthetic outcome on the long term was largely dependent on a good initial reconstruction.…”
Section: Surgical Treatment Of Nonsyndromic Craniosynostosismentioning
confidence: 99%
See 2 more Smart Citations
“…Selber 120 found that the use of interpositional bone grafts in a series of 68 metopic children led to a decrease in the development of temporal dents. In a population of 92 trigonocephaly children in which no bone graft was used, Van der Meulen, 101 however, observed an automatic growth correction of the hypotelorism on x-ray, on account of which the use of an interpositional bone graft was judged to be unnecessary. From a photographic evaluation of 45 patients, Hilling 123 concluded that a satisfactory esthetic outcome on the long term was largely dependent on a good initial reconstruction.…”
Section: Surgical Treatment Of Nonsyndromic Craniosynostosismentioning
confidence: 99%
“…The other end of the spectrum is characterized by a wedge-shaped forehead with hypotelorism and supraorbital retrusion on the basis of decreased growth of the forehead widthwise. 101 …”
Section: Surgical Treatment Of Nonsyndromic Craniosynostosismentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal hollowing seemed to be the most commonly seen postoperative abnormality, which coincided with a notably reduced postoperative growth rate of the bony temporal region [97]. A subsequent study confirmed that reduced bone growth (and not soft tissue factors) was the major contributor to this temporal hollowing [99].…”
Section: Fronto-supra-orbital Advancement and Remodellingmentioning
confidence: 99%
“…[19] Reason for premature fusion of the metopic suture may be one or combination of following-Intrauterine compression; from the subjacent dura mater supplying osteoinductive growth factors and cellular elements to the suture mesenchyme; exposure to high level of thyroxine resulting from maternal, juvenile, or neonatal hyperthyroidism; deficient brain growth; primary abnormality of mesenchyme; rickets; hypercalcemia; and or gene mutation. [2122232425262728]…”
Section: Discussionmentioning
confidence: 99%